2020
DOI: 10.3390/ijms21197283
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics and Bioinformatics Analyses Reveal Key Roles of GSK-3 and AKAP4 in Mouse Sperm Capacitation

Abstract: Protein phosphorylation can induce signal transduction to change sperm motility patterns during sperm capacitation. However, changes in the phosphorylation of sperm proteins in mice are still incompletely understood. Here, capacitation-related phosphorylation in mouse sperms were firstly investigated by label-free quantitative (LFQ) phosphoproteomics coupled with bioinformatics analysis using ingenuity pathway analysis (IPA) methods such as canonical pathway, upstream regulator, and network analysis. Among 163… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The regulation Frontiers in Physiology frontiersin.org of protein phosphorylation during capacitation and AR is crucial to sperm function, and moreover, increased levels of tyrosine phosphorylation are considered a marker of capacitation (Morgan et al, 2008;Kwon et al, 2014). In order to understand the overall regulation of phosphorylation during sperm capacitation, some studies have used phosphoproteomics techniques to quantify the changes in phosphorylation sites levels in mice (Platt et al, 2009;Chung et al, 2014;Syifa et al, 2020), rats (Baker et al, 2010)and humans (Wang et al, 2015). Furthermore, to the best of our knowledge, AR has not yet been studied from the perspective of phosphorylated proteomics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation Frontiers in Physiology frontiersin.org of protein phosphorylation during capacitation and AR is crucial to sperm function, and moreover, increased levels of tyrosine phosphorylation are considered a marker of capacitation (Morgan et al, 2008;Kwon et al, 2014). In order to understand the overall regulation of phosphorylation during sperm capacitation, some studies have used phosphoproteomics techniques to quantify the changes in phosphorylation sites levels in mice (Platt et al, 2009;Chung et al, 2014;Syifa et al, 2020), rats (Baker et al, 2010)and humans (Wang et al, 2015). Furthermore, to the best of our knowledge, AR has not yet been studied from the perspective of phosphorylated proteomics.…”
Section: Discussionmentioning
confidence: 99%
“…This fully demonstrated that serine/threonine also plays a crucial role during sperm capacitation. However, the phosphorylation research on sperm capacitation has mainly focused on tyrosine so far, with few reports on serine/threonine ( Chung et al, 2014 ; Wang et al, 2015 ; Syifa et al, 2020 ). All these changes occurred before the AR, which is a Ca 2+ dependent process ( Buffone et al, 2008 ), including the activation of phospholipases C and A2 as well as PKC and cAMP-dependent protein kinase pathways, implying that protein phosphorylation plays a major role in the secondary messenger regulatory mechanism of AR ( Benoff, 1998 ; Topfer-Petersen et al, 2000 ; Urner and Sakkas, 2003 ; Ashizawa et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in calcium ion permeability is followed by the increase in the strength and speed of sperm flagellum moving for a swim [29]. Faster spermatozoa have higher energy needs derived from cAMP-dependent tyrosine phosphorylation in the mitochondria, producing ROS [77]. Low ROS levels also trigger and regulate a series of events, including protein phosphorylation for capacitation [78].…”
Section: )mentioning
confidence: 99%
“…Capacitation is an essential physiological prerequisite for sperm cell acrosome reaction and oocyte fertilization. During capacitation, the plasma membrane's destabilization prepares the sperm's tip for acrosome reaction [77]. The cryo-capacitated sperm plasma membrane is fragile and unresistant to spontaneous acrosome reaction and deterioration and fails to fertilize an ovum [83].…”
Section: )mentioning
confidence: 99%
“…An example of the crucial role exerted by phosphorylation in physiological conditions is reported by Syifa and colleagues. They ran a phosphoproteome analysis of mouse sperm during capacitation that led to the identification of 1050 new phosphorylated sites in 402 proteins potentially involved in sperm motility, outlining the role of GSK-3α and AKAP4 in mouse sperm capacitation [ 6 ].…”
mentioning
confidence: 99%